Huck Runs Amuck! - Taylor, Sean 1965-; Reynolds, Peter 1961- (New York : Dial Books for Young Readers, 2011)
The residents of North Skettykolk are no match for a visiting mountain goat with an enormous appetite for flowers.
Keywords: Mountain goats -- Fiction; Goats -- Fiction; Flowers -- Fiction; Fiction